Application of power electronic components to control parameters and switching of compensation devices on power networks - Hiep, Pham Van; Hoa, Pham Van; Viet, Nguyen Quang (VNU Journal of Science: Mathematics - Physics; Vol 25 No 2, 2009)
Abstract